Positive Youth Development: A commitment, an opportunity, a challenge: Book Review:“Handbook of Positive Youth Development. Advancing Research, Policy and Practice in Global Contexts” - Martín Carbonell, Marta de la Caridad (Pensando Psicología, 2021)
The text presented, published by Editorial Springer, is an unprecedented collection, which has managed to gather the complete and inclusive empirical evidence on PYD to date, with data from 38 countries representing the voices of 22,083 young people and emerging adults. From almost all regions of the world, allowing the reader to come into contact with vast geographic regions (Europe, Asia, Africa, the Middle East, Australia, New Zealand, and the North, Central and South Americas); and with new international perspectives. The people responsible for compiling and organizing this monumental work have been the Editors: Radosveta Dimitrova, from Stockholm University, and Nora Wiium, from the University of Bergen, Norway. Note that Radosveta Dimitrova in 2016 received the award from the Society for the Study of Behavioral Development-ISSBD for her theoretical contributions and for her scientific outreach work. For her part, Nora Wiium, since 2014 has been leading the International Positive Youth Development Project (PYD) that integrates collaborations from more than 30 countries on all continents.